2016
DOI: 10.1002/ijc.30142
|View full text |Cite
|
Sign up to set email alerts
|

Subtype‐specific micro‐RNA expression signatures in breast cancer progression

Abstract: Robust markers of invasiveness may help reduce the overtreatment of in situ carcinomas. Breast cancer is a heterogeneous disease and biological mechanisms for carcinogenesis vary between subtypes. Stratification by subtype is therefore necessary to identify relevant and robust signatures of invasive disease. We have identified microRNA (miRNA) alterations during breast cancer progression in two separate datasets and used stratification and external validation to strengthen the findings. We analyzed two separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 58 publications
0
55
0
1
Order By: Relevance
“…A-C, E, and F, Mann-Whitney U test; D, Kruskal-Wallis test. ETP, early T-cell precursor leukemia; BM, bone marrow; PB, peripheral blood been modulated in solid tumors, like gallbladder carcinoma 51 and breast cancer, 52 and its downregulation is associated with metastasis and cell proliferation. 51 Besides genetic abnormalities observed in Band T-cell leukemias, distinct posttranscriptional regulation of leukemogenic genes may be present yielding different molecular mechanisms of growth and malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…A-C, E, and F, Mann-Whitney U test; D, Kruskal-Wallis test. ETP, early T-cell precursor leukemia; BM, bone marrow; PB, peripheral blood been modulated in solid tumors, like gallbladder carcinoma 51 and breast cancer, 52 and its downregulation is associated with metastasis and cell proliferation. 51 Besides genetic abnormalities observed in Band T-cell leukemias, distinct posttranscriptional regulation of leukemogenic genes may be present yielding different molecular mechanisms of growth and malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The let-7 family comprises known tumor suppressors and participates in the regulation of stemness in breast cancer cells. 14,18 In addition, previous studies have shown that, as a key enzyme in the biogenesis of miRNA, dysfunction of Dicer1 leads to low expression of the let-7 family. 19 In this regard, we next explored whether Dicer1 affects regulation of the let-7 family in EC.…”
Section: Let-7 Family Is Involved In the Regulation Of Dicer1 To Ec Smentioning
confidence: 99%
“…miRNAs play crucial roles in the regulation of cancer-associated processes such as proliferation, apoptosis, and differentiation, and are known to elicit context-and cell-type specific expression [8,9]. In breast cancer, expression of miRNAs has been associated with clinical and molecular subtypes [10][11][12], progression [13][14][15], prognosis [16,17] and expression of oncogenes [18]. Importantly, miRNAs have been shown to regulate the expression of epigenetic regulators such as DNMTs and TETs [19,20].…”
Section: Introductionmentioning
confidence: 99%